2020
DOI: 10.3390/ma13020414
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Parts Fabricated by Laser-Foil-Printing Additive Manufacturing: Processing, Microstructure, and Mechanical Properties

Abstract: Fabrication of dense aluminum (Al-1100) parts (>99.3% of relative density) by our recently developed laser-foil-printing (LFP) additive manufacturing method was investigated as described in this paper. This was achieved by using a laser energy density of 7.0 MW/cm2 to stabilize the melt pool formation and create sufficient penetration depth with 300 μm thickness foil. The highest yield strength (YS) and ultimate tensile strength (UTS) in the LFP-fabricated samples reached 111 ± 8 MPa and 128 ± 3 MPa, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This faster heat conduction in LFP prevents creation of large pores, as the generated gas bubbles in the melt pool do not get long enough time to grow in size. This higher cooling rate adjusts the parts' microstructure, resulting in less porosity and higher mechanical properties, as extensively discussed in our previous published work (Hung et al, 2020). A solution to improve the challenge of low heat transfer in the L-PBF process has been reported in the literature through preheating the build plate which helped uniforming the temperature distribution around the melt pool; results showed that preheating the build platform to 150°C decreased the porosity and significantly improved the material's ductility due to the more homogenized cellular microstructure (Nezhadfar et al, 2021).…”
Section: Mechanical Propertiesmentioning
confidence: 66%
See 4 more Smart Citations
“…This faster heat conduction in LFP prevents creation of large pores, as the generated gas bubbles in the melt pool do not get long enough time to grow in size. This higher cooling rate adjusts the parts' microstructure, resulting in less porosity and higher mechanical properties, as extensively discussed in our previous published work (Hung et al, 2020). A solution to improve the challenge of low heat transfer in the L-PBF process has been reported in the literature through preheating the build plate which helped uniforming the temperature distribution around the melt pool; results showed that preheating the build platform to 150°C decreased the porosity and significantly improved the material's ductility due to the more homogenized cellular microstructure (Nezhadfar et al, 2021).…”
Section: Mechanical Propertiesmentioning
confidence: 66%
“…To eliminate the surface roughness effect on the mechanical properties, the tensile specimens were cut from the LFP-fabricated parts using wire electrical discharge machining. The miniature tensile bar has dimensions shown in Figure 3, following American Society for Testing and Materials standards (Hung et al, 2020;Kolhatkar et al, 2019). An Instron machine was used to measure the tensile specimens with a clip-on extensometer at the crosshead speed of 0.015 1/min (strain rate per minute) (Jirandehi and Khonsari, 2021;Ghadimi et al, 2021).…”
Section: Experimental Measurementsmentioning
confidence: 99%
See 3 more Smart Citations